2013
DOI: 10.1016/j.archoralbio.2013.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Genes expressed in dental enamel development are associated with molar-incisor hypomineralization

Abstract: Genetic disturbances during dental development influence variation of number and shape of the dentition. In this study, we tested if genetic variation in enamel formation genes is associated with molar-incisor hypomineralization (MIH), also taking into consideration caries experience. DNA samples from 163 cases with MIH and 82 unaffected controls from Turkey, and 71 cases with MIH and 89 unaffected controls from Brazil were studied. Eleven markers in five genes [ameloblastin (AMBN), amelogenin (AMELX), enameli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
185
1
18

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 178 publications
(210 citation statements)
references
References 45 publications
6
185
1
18
Order By: Relevance
“…It is worth mentioning that genetic variants, even as subtle as single nucleotide polymorphisms in intronic region, in candidate enamel formation genes in this study, have been reported to influence other dental conditions, such as amelogenesis imperfecta or molar-incisor hypomineralization. 23 It strongly supports the hypothesis that even minor alterations in gene structure could influence protein function and impact the enamel growth and mineralization and, therefore, alter individual's susceptibility to caries alongside of the environmental factors. Another possibility is that the SNPs could be in linkage to genetic variants outside the region of interest, but testing the actual influence of non-coding SNPs on protein function and analysis of linkage disequilibrium throughout the genome is still not a simple task.…”
Section: Discussionsupporting
confidence: 69%
“…It is worth mentioning that genetic variants, even as subtle as single nucleotide polymorphisms in intronic region, in candidate enamel formation genes in this study, have been reported to influence other dental conditions, such as amelogenesis imperfecta or molar-incisor hypomineralization. 23 It strongly supports the hypothesis that even minor alterations in gene structure could influence protein function and impact the enamel growth and mineralization and, therefore, alter individual's susceptibility to caries alongside of the environmental factors. Another possibility is that the SNPs could be in linkage to genetic variants outside the region of interest, but testing the actual influence of non-coding SNPs on protein function and analysis of linkage disequilibrium throughout the genome is still not a simple task.…”
Section: Discussionsupporting
confidence: 69%
“…Recent research has indicated that etiology of MIH is multicasual and that genetic variations can, in combination with different environmental factors, play a significant role in the occurrence of these structural enamel defects 20 . Clinical manifestation of MIH shows great variability in the number of affected teeth and severity of hypomineralized changes.…”
Section: Prikaz Slučaja Pacijentmentioning
confidence: 99%
“…Bu olay mine kristallerinin enine büyümesini hızlandırarak genişliğinin artması-nı sağlamaktadır. KLK4 geninde meydana gelen mutasyonların da BAKH oluşumunda rol oynadığı yapılan çalışmalarla desteklenmiştir (26,27). Yapılan bir başka araştırmaya göre BAKH üzerinde etkili olan bir başka protein ise SCUBE1 proteinidir (28).…”
Section: Etiyolojisiunclassified